POLA KOMUNIKASI KOMUNITAS DELTA PUNK ART SEBAGAI KAUM MARJINAL DALAM RELASI SOSIAL MASYARAKAT KOTA SIDOARJO (Universitas Negeri Surabaya, 2022)
This research on communication patterns of the Delta Punk Art community as marginal people in the social relations of the people of Sidoarjo City is intended to find out how the communication patterns that occur in their activities are directly related to the community. In this case, the pattern of communication is interpreted as a communicative style, both verbal and non-verbal forms. This study uses the ethnographic method of communication with the aim of facilitating data collection by focusing on communication activities that occur in the activities held, which consist of communicative situations, communicative events, and communicative acts. Data were collected through participant observation and interviews. The results of this study indicate a relaxed and friendly communication style in the form of the use of verbal words in Javanese Suroboyo-an and social language. While the non-verbal communication style is used to give the impression of closeness, togetherness, and a spirit for independence. There is also a shift in the meaning of resistance to the punk ideology adopted by the Delta Punk Art community.